2009
DOI: 10.1007/s00264-009-0899-6
|View full text |Cite
|
Sign up to set email alerts
|

Alumina-on-alumina ceramic versus metal-on-highly cross-linked polyethylene bearings in total hip arthroplasty: a comparative study

Abstract: The aim of the study was to evaluate the reliability and durability of alumina-on-alumina ceramic in comparison to metal-on-highly cross-linked polyethylene (CoCr/HXLPE) bearing couples. This prospective randomised study involved 150 patients (157 hips). All patients (mean age: 54.7 years) obtained an identical fibre metal midcoat femoral stem and fibre metal-coated acetabular shell. In 78 patients (82 hips) we used alumina, while in 72 patients (75 hips) metal-polyethylene bearing couples were used. During a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 21 publications
2
38
0
4
Order By: Relevance
“…In this series, cementless fully hydroxyapatite coated implants with ceramic and ceramic bearings provided very encouraging results at medium follow-up. This study is in line with previous reports with shorter or similar follow-up [13,15,18,19].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In this series, cementless fully hydroxyapatite coated implants with ceramic and ceramic bearings provided very encouraging results at medium follow-up. This study is in line with previous reports with shorter or similar follow-up [13,15,18,19].…”
Section: Discussionsupporting
confidence: 83%
“…To date, limited data is available regarding medium-to long-term follow-up of ceramic-on-ceramic uncemented total hip arthroplasty [5,7,[13][14][15][16][17][18][19] (Table 1). The longest follow-up reported with ceramic-on-ceramic bearing is 18.5 years [5], including different designs of implants: cemented, uncemented and hybrid implants.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies to reduce wear have focused on improvements in the bearing surface such as ceramic-onceramic or ceramic-on-highly cross-linked polyethylene bearings. Several studies have demonstrated that contemporary ceramic-on-ceramic or ceramic-on-highly cross-linked polyethylene bearings are associated with low prevalence of osteolysis in young and active patients [3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…At both stages of selection, we estimated chance-adjusted agreement statistics among reviewers with a j statistic (j = 0.917 for abstract review; j = 1.000 for full-text review), and all disagreements were settled by the opinion of a third senior reviewer (GAN-M). Eleven articles [2,4,5,8,14,22,28,33,40,41,49] were deemed eligible through this process and seven studies [9,[16][17][18][19][20][21] were added following a manual search of the bibliographies of the 11 chosen articles for a final study cohort of 18 manuscripts (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%